EFFECT OF ADDING CALCIUM HYDROXIDE Ca(OH)2 ON MOLTING, GROWTH AND SURVIVAL RATE VANNAMEI SHRIMP (LITOPENAEUS VANNAMEI) - Wiwi Yulihartini; Rusliadi '; Hamdan Alawi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was carried out on June 01 - June 30, 2016 at the Brackish water Aquaculture Institution Shrimp Hatchery Unit, Gelung, Situbondo, East Java. The purpose of this study was to determine the effect of calcium hydroxide Ca(OH)2 dose on moulting, growth and survival rate of vannamei shrimp (Litopenaeus vannamei) juveneli. The method used in this research was the experimental method, using one factor completely randomized design with 6 treatments and 3 replications. P0 (control) without giving ( 0 mg/L Ca(OH) 2), P1 (Dose Ca(OH)2 1 mg / L of water), P2 (Dose Ca(OH)2 2 mg / L of water), P3 (Dose Ca(OH)2 3 mg / L water ), P4 (dose Ca(OH)2 4 mg / L of water) and P5 (dose Ca (OH) 2 5 mg / L of water). The results showed that administration of calcium hydroxide Ca(OH)2 at a dose of 60 mg / L of water. Absolute growth was 0.56 g, 2.06 cm, daily growth rate 1.73% and survival rate was 68.33%. The hiqhest pucentage % moulting in 28 days realing was about 50 % mared at 60 mg/L Ca(OH)2.Keywords: Vannamei, Calsium Hydroxide Ca(OH) 2, growth and survival